2016
DOI: 10.1093/nar/gkw832
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of LSD1 and HDAC3 in STAT5-dependent transcription is determined by protein interactions, binding affinities, motifs and genomic positions

Abstract: STAT5 interacts with other factors to control transcription, and the mechanism of regulation is of interest as constitutive active STAT5 has been reported in malignancies. Here, LSD1 and HDAC3 were identified as novel STAT5a interacting partners in pro-B cells. Characterization of STAT5a, LSD1 and HDAC3 target genes by ChIP-seq and RNA-seq revealed gene subsets regulated by independent or combined action of the factors and LSD1/HDAC3 to play dual role in their activation or repression. Genes bound by STAT5a al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Recently, LSD1 and HDAC3 have been shown to interact with STAT5A. Immunoprecipitation experiments were conducted using nuclear extracts from IL-3 stimulated pro-B Ba/F3 cells with BirA biotinylated STAT5A [63]. The specific binding regions were determined using 35S-LSD1 and 35S-HDAC3 pull-downs with GST-STAT5A sub-fragments.…”
Section: Stat5 Interacting Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, LSD1 and HDAC3 have been shown to interact with STAT5A. Immunoprecipitation experiments were conducted using nuclear extracts from IL-3 stimulated pro-B Ba/F3 cells with BirA biotinylated STAT5A [63]. The specific binding regions were determined using 35S-LSD1 and 35S-HDAC3 pull-downs with GST-STAT5A sub-fragments.…”
Section: Stat5 Interacting Proteinsmentioning
confidence: 99%
“…LSD1 was shown to interact with the DNA-binding linker and the SH2 domain. HDAC3 was shown to interact with the DNA-binding linker, SH2 domain, and the coiled coil domain [63] (refer to Figure 3). ChIP-seq experiments have shown that STAT5A, LSD1, and HDAC3 have many overlapping binding regions within the genome [63].…”
Section: Stat5 Interacting Proteinsmentioning
confidence: 99%
See 3 more Smart Citations